2015
DOI: 10.1093/trstmh/tru200
|View full text |Cite
|
Sign up to set email alerts
|

An innovative ecohealth intervention for Chagas disease vector control in Yucatan, Mexico

Abstract: BackgroundNon-domiciliated (intrusive) triatomine vectors remain a challenge for the sustainability of Chagas disease vector control as these triatomines are able to transiently (re-)infest houses. One of the best-characterized examples is Triatoma dimidiata from the Yucatan peninsula, Mexico, where adult insects seasonally infest houses between March and July.MethodsWe focused our study on three rural villages in the state of Yucatan, Mexico, in which we performed a situation analysis as a first step before t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 46 publications
1
57
0
3
Order By: Relevance
“…For instance, modelling studies have suggested that vector control interventions based on insecticide spraying would not be suitable, particularly because of the necessity to spray insecticide yearly during a reduced period of time in the year, almost operationally impossible [24]. Alternative control intervention strategies, based on the Ecohealth principles, have recently been implemented at different pilot scales [15, 16, 25] and are currently giving promising results (Waleckx et al, unpublished data). While T. dimidiata generally does not establish colonies inside human dwellings in the Yucatán Peninsula, in other parts of its geographical distribution, such as in Guatemala, populations are well domiciliated, as evidenced by bug collections throughout the country showing high infestation and colonization indexes [10, 26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, modelling studies have suggested that vector control interventions based on insecticide spraying would not be suitable, particularly because of the necessity to spray insecticide yearly during a reduced period of time in the year, almost operationally impossible [24]. Alternative control intervention strategies, based on the Ecohealth principles, have recently been implemented at different pilot scales [15, 16, 25] and are currently giving promising results (Waleckx et al, unpublished data). While T. dimidiata generally does not establish colonies inside human dwellings in the Yucatán Peninsula, in other parts of its geographical distribution, such as in Guatemala, populations are well domiciliated, as evidenced by bug collections throughout the country showing high infestation and colonization indexes [10, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Males, females, and N5 nymphs (fifth-instar nymphs) of uninfected laboratory-reared T. dimidiata originating from triatomines collected in the field within the framework of experimental vector control interventions [15, 16] in the rural villages of Bokobá (21°00’27”N, 89°10’47”W), Teya (21°02’55”N, 89°04’25”W) and Sudzal (20°52’19”N, 88°59’20”W), were used. The bugs, maintained by feeding every 2–3 weeks on pigeons, were starved for 10–15 days before being used in the experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The geographical distribution of Triatominae and their increased tolerance to modified habitats have boosted human contact, which is expected to increase in the future in both rural and urban populations (Enger et al ., ; Walter et al ., ; Ibarra‐Cerdeña et al ., ; López‐Cancino et al ., ; Ramsey et al ., ). Although lower rural vector exposure is expected in the U.S.A. due to lifestyle, sanitation, and demographics, it remains high in rural and even in high income urban areas in Mexico (Ramsey et al ., ; Torres‐Montero et al ., ; Waleckx et al ., ). Only one species in NA, Triatoma sanguisuga (Leconte, 1855), occurs exclusively in the U.S.A., whereas the two countries share 13 species (and eight subspecies), including 11 from the protracta , lecticularia and rubida complexes, only distributed within the Nearctic region.…”
Section: Introductionmentioning
confidence: 97%
“…28 This appears confirmed by the lack of association between intradomiciliary insecticide spraying and the seropositivity of inhabitants against Trypanosoma cruzi in the Amazon region. 8 Thus, alternative vector control intervention, such as the use of insect screens, 29,30 need to be considered to reduce or prevent human-vector contact in these conditions.…”
Section: Discussionmentioning
confidence: 99%